2018
DOI: 10.1007/s00268-018-4637-3
|View full text |Cite
|
Sign up to set email alerts
|

Does Intermittent Pringle Maneuver Increase Postoperative Complications After Hepatectomy for Hepatocellular Carcinoma? A Randomized Controlled Trial

Abstract: ClinicalTrials.gov NCT01759901.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 33 publications
2
37
1
5
Order By: Relevance
“…After browsing titles and abstracts, 439 records were excluded, including 38 were for lack of comparison, 66 were for benign disease, 20 were for data unavailable, 66 were for palliative treatment, 168 were for not specified for HCC, 45 were for in vitro studies, 36 were for reviews. Among the remained 109 records, 103 records were excluded for comparison PM with selective PM, Finally, six researches [21,22,27,28,29,30] were included for analysis. Details were depicted specifically in Fig 1. In total, 5275 patients were enrolled in this meta-analysis, with 3290 cases in the IPM group and 1985 cases in the non-IPM group.…”
Section: Base Characteristic Of the Included Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…After browsing titles and abstracts, 439 records were excluded, including 38 were for lack of comparison, 66 were for benign disease, 20 were for data unavailable, 66 were for palliative treatment, 168 were for not specified for HCC, 45 were for in vitro studies, 36 were for reviews. Among the remained 109 records, 103 records were excluded for comparison PM with selective PM, Finally, six researches [21,22,27,28,29,30] were included for analysis. Details were depicted specifically in Fig 1. In total, 5275 patients were enrolled in this meta-analysis, with 3290 cases in the IPM group and 1985 cases in the non-IPM group.…”
Section: Base Characteristic Of the Included Studiesmentioning
confidence: 99%
“…The characteristic and quality of the included trials were shown in Table 1. However, only one RCT [29] was eligible. The scores ranged from 7 to 8, indicating that all the studies were of high quality (Table 1).…”
Section: Base Characteristic Of the Included Studiesmentioning
confidence: 99%
See 3 more Smart Citations